Aphodiinae described or recorded by Bates in Biologia Centrali-Americana (Coleoptera Scarabaeoidea: Aphodiidae) - Dellacasa, Marco; Gordon, Robert D.; Dellacasa, Giovanni (Instituto de Ecología, A.C., 2002)
Species of Aphodius described or recorded by Bates (1887, 1889) in the Biologia Centrali-Americana are discussed, resulting in some new combinations or new status as follows: Aphodius dugesi Bates, 1887 = Diapterna dugesi (Bates, 1887) n. comb.; Aphodius sallei Harold, 1863 = Agrilinus sallei (Harold, 1863) n. comb.; Aphodius lansbergei Harold, 1874 = Agrilinus lansbergei (Harold, 1874) n. comb.; Aphodius indutilis Harold, 1874 = Agrilinus indutilis (Harold, 1874) n. comb.; Aphodius azteca Harold, 1863 = Agrilinus (s. l.) azteca (Harold, 1863) n. comb.; Aphodius oleosus Harold, 1871 = Pharaphodius (s. l.) oleosus (Harold, 1871) n. comb.; Aphodius innexus Say, 1835 = Liothorax innexus (Say, 1835) n. comb.; Aphodius cruentatus LeConte, 1878 = Agoliinus (s. l.) cruentatus (LeConte, 1878) n. comb.; Aphodius glyptus Bates, 1887 = Trichonotuloides glyptus (Bates, 1887) n. comb.; Aphodius latecrenatus Bates, 1887 = Trichonotuloides latecrenatus (Bates, 1887) n. comb.; Aphodius euprosopus Bates, 1887 = Agrilinus (s. l.) azteca ab. euprosopus (Bates, 1887) n. stat. and n. comb.; Aphodius constricticollis Bates, 1889 = Imelda constricticollis (Bates, 1889) n. comb.; Aphodius opisthius Bates, 1887 (new name for Aphodius duplex Bates, 1887) = Gonaphodiellus opisthius (Bates, 1887) n. comb.; Aphodius panamensis Harold, 1859 = Aidophus panamensis (Harold, 1859) n. comb. [Didactyliini]; Aphodius guatemalensis Bates, 1887 = Blackburneus (s. l.) guatemalensis (Bates, 1887) n. comb.; Aphodius guatemalensis var. scotinus Bates, 1887 = Blackburneus (s. l.) guatemalensis ab. scotinus (Bates, 1887) n. comb.; Aphodius guatemalensis var. chiriquinus Bates, 1887 = Blackburneus (s. l.) guatemalensis ab. chiriquinus (Bates, 1887) n. comb.; Aphodius charmionus Bates, 1887 = Blackburneus (s. l.) charmionus (Bates, 1887) n. comb.; Aphodius diminutus Bates, 1887 = Blackburneus (s. l.) diminutus (Bates, 1887) n. comb.; Aphodius erythrinus Bates, 1887 = Blackburneus (s. l.) erythrinus (Bates, 1887) n. comb.; Aphodius xanthus Bates, 1887 = Blackburneus (s. l.) xanthus (Bates, 1887) n. comb.; Aphodius larreae Horn, 1887 (senior synonym of Aphodius bifrons Bates, 1887) = Drepanocanthoides larreae (Horn, 1887) n. comb.; Aphodius hogei Bates, 1887 = Cephalocyclus hogei (Bates, 1887) n. comb.; Aphodius hogei var. durangoensis Bates, 1887 = Cephalocyclus durangoensis (Bates, 1887) n. stat. and n. comb. Moreover, the new combination for Aphodius pseudolividus Balthasar, 1941 is Labarrus pseudolividus (Balthasar, 1941). The new genus Imelda is described with Aphodius constricticollis as the type species. Aphodius (Trichonotuloides) fossulatipennis Balthasar, 1945 is considered a junior synonym of Trichonotuloides latecrenatus (Bates, 1887); and Aphodius omiltemius Bates, 1889 is placed as a junior synonym of Cephalocyclus mexicanus (Harold, 1862). Lectotypes and paralectotypes are designated where necessary.